2022
DOI: 10.1101/2022.06.09.22275942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutralising antibodies predict protection from severe COVID-19

Abstract: Background: Vaccine protection from COVID-19 has been shown to decline with time-since-vaccination and against SARS-CoV-2 variants. Protection against severe COVID-19 is higher than against symptomatic infection, and also appears relatively preserved over time and against variants. Although Protection protection from symptomatic SARS-CoV-2 infection has been shown to be strongly correlated with neutralising antibody titres, however, this relationship has been is less well described for severe COVID-19. Protect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…This may indicate that, while SARS-CoV-2 pathogenicity continues to fluctuate and may evolve away from the attenuated pathogenicity observed in BA.1 33 , the increased population immunity may keep disease severity relatively low 34 . Consistent with this, a recent analysis showed that neutralization capacity required to prevent severe disease is considerably lower than that required to prevent symptomatic infection 35 . In addition, there may be factors specific to the South African infection environment which reduce pathogenicity such as immunity from Beta infection combined with vaccination, which we found to broaden neutralization capacity against BA.4 and BA.5 23 .…”
Section: Resultsmentioning
confidence: 65%
“…This may indicate that, while SARS-CoV-2 pathogenicity continues to fluctuate and may evolve away from the attenuated pathogenicity observed in BA.1 33 , the increased population immunity may keep disease severity relatively low 34 . Consistent with this, a recent analysis showed that neutralization capacity required to prevent severe disease is considerably lower than that required to prevent symptomatic infection 35 . In addition, there may be factors specific to the South African infection environment which reduce pathogenicity such as immunity from Beta infection combined with vaccination, which we found to broaden neutralization capacity against BA.4 and BA.5 23 .…”
Section: Resultsmentioning
confidence: 65%
“…They included data from the Sanofi-GlaxoSmithKline, Moderna, and Pfizer-BioNTech vaccine constructs incorporating the Beta, Delta, or Omicron BA.1 spike proteins (either alone or in combination with each other or the ancestral variant spike proteins). We then used a validated model relating neutralisation titres to vaccine effectiveness to estimate the changes in vaccine protection under different booster regimens [9][10][11] .…”
Section: Main Textmentioning
confidence: 99%
“…Similar analyses can be used to predict comparative vaccine effectiveness against severe COVID-19 under the same assumption. A population with 50% protection from symptomatic infection is predicted to have 86.6% protection from severe COVID-19 9,11 . Boosting with an ancestral-based booster that increases neutralising antibody titres by 11-fold is expected to increase this to an average of 98% protection from severe disease over the six month period following boosting, and a variant-modified booster producing 1.5-fold higher neutralising antibody titres would increase protection to an average of 98.8% (i.e.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…It is however worth to note that the majority of SARS-CoV-2 neutralizing antibodies target the RBD region, whilst deletion of NTD antibodies have minimal impact on neutralization 28 . b) We have focused on neutralizing activity, which is the only known correlate of protection so far 1,29 . But it is likely that T cell responses 8 and non-neutralizing antibody and functions 9,10 also contribute to protection against severe disease.…”
Section: Discussionmentioning
confidence: 99%